COOPERATIVE LEARNING:benefits and challenges according to the English teacher - Hermawan, Heri; Syahrul; Ibnumal (English Language Teaching Methodology, 2024)
Cooperative learning fosters collaborative environments where students actively engage with their peers, promoting mutual support and shared responsibility in achieving learning objectives. The objectives of this research are formulated to identify the benefits and challenges of the implementation of cooperative learning in SMAN 16 Pangkep according to the English teacher. A case study research methodology was used in the study. A case study is a technique that allows one to fully understand a topic or event in a real-world setting. It is a popular study approach in many different fields. A case study is a thorough examination of a person, group, or society in which the researcher looks at a lot of information on a lot of different things. Although not always, case study data are typically in a qualitative style. The effectiveness of a teaching method is contingent upon various factors, including the specific context, learning objectives, and the preferences of both teachers and students. While cooperative learning has demonstrated efficacy in numerous scenarios, it is recognized that alternative methods may also be suitable depending on the unique needs and characteristics of the class. This highlights the value of educators being open to exploring and adapting different instructional strategies to best meet the requirements of their students.